Reflections on Career Pathways of Simulation-Focused Experts in the Field - Sanko, J.S.; Calhoun, A.W.; Issenberg, S.B.; Kelly, Michelle; Battista, A. (LIPPINCOTT WILLIAMS & WILKINS, 2020)
STATEMENT: This article presents reflections of career pathways of simulation researchers as well as a discussion of the themes found in the stories presented. It is the intent of the authors to present and foster a discussion around the ways in which we as a simulation community wish to promote recognition of scholarship among simulation researchers and help support newcomers find success as simulation researchers in academia. We also present recommendations for those considering entering the field based on tactics that were successful and not successful among the scholars who shared their stories.